Numerical Solution of Fractional Partial Differential Equations by Discrete Adomian Decomposition Method (Advances in Applied Mathematics and Mechanics, 2014)
In this paper we find the solution of linear as well as nonlinearfractional partial differential equations using discrete Adomiandecomposition method. Here we develop the discrete Adomian decompositionmethod to find the solution of fractional discrete diffusion equation,nonlinear fractional discrete Schrodinger equation, fractional discreteAblowitz-Ladik equation and nonlinear fractional discrete Burger's equation.The obtained solution is verified by comparison with exact solution when $α=1$.